2022
DOI: 10.3934/agrfood.2022030
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of fresh rice straw silage quality prepared with addition of lactic acid bacteria and crude cellulase

Abstract: <abstract> <p>The objective of this study was to determine the characteristics of fresh rice straw silage quality prepared with addition of <italic>Lactiplantibacillus plantarum</italic> 1A-2 and crude cellulase alone or in combination. Quality of the silage was observed through the chemical composition, chemical structure and <italic>in vitro</italic> digestibility. Six treatments were used in this study, i.e., 1) rice straw without any treatment as control, 2) rice straw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The previous research indicated a 14%–16% yield for chitosan extract derived from silkworm pupae [ 16 , 29 ]. Although silkworm chitosan yields less than crustacean-derived chitosan (18.33% and 17.20% for shrimp and crab, respectively) [ 32 , 33 ], it is still a valuable source. The low chitosan content in silkworm pupae is due to their high lipid and protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous research indicated a 14%–16% yield for chitosan extract derived from silkworm pupae [ 16 , 29 ]. Although silkworm chitosan yields less than crustacean-derived chitosan (18.33% and 17.20% for shrimp and crab, respectively) [ 32 , 33 ], it is still a valuable source. The low chitosan content in silkworm pupae is due to their high lipid and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…The low chitosan content in silkworm pupae is due to their high lipid and protein levels. The low chitosan yield in insects, including this one, can be attributed to their high lipid and protein content [ 32 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding L. plantarum Ca098 reduces the pH quickly and increases the concentration of lactic acid compared to L. plantarum 1A-2; the fermented rice straw produced had a higher crude protein content than other treatments. The use of L. plantarum 1A-2 inoculant was reported to produce silage with good and stable quality on elephant grass [20], corn crops [21], and rice straw [22].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the interaction of cellulase with LAB to improve the quality of silages has been extensively studied, and the advantages in increasing dry matter, crude protein and lactic acid contents, and decreasing acid detergent fiber (ADF) and neutral detergent fiber (NDF) contents have been verified. The silages include fresh rice straw silage ( Sarwono et al, 2021 ), oat silage ( Xu et al, 2022 ), Caragana korshinskii silage ( Bai et al, 2023 ), mulberry leaf silage ( Lactobacillus ) ( He et al, 2019 ), a mixture of amaranth and rice straw ( Lactobacillus plantarum ) ( Mu et al, 2020 ), and mixed silage of whole-plant corn and peanut Vines ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%